An Analysis of Translation Technique Used in The Fantasy Novel “Overlord” - Gde Wetan Pragena Anggara; Diah Supatmiwati; Muhammad Zaki Pahrul Hadi (LPPM Universitas Bumigora Mataram, 2023)
This research aim is to know what type of translation technique that is used in translating the fantasy and game term in the fantasy novel “Overlord”. Translation is really important when it comes to information, culture, message, etc between two or more different people who use different language. However, the problem arises when it comes to translate a fantasy stories or games because the translation technique is heavily relied on the culture. Meanwhile, the fantasy stories and games are usually not bounded by one specific culture. This is why this research is needed to be conducted, to answer the question regarding which translation technique that the translator used to approach the fantasy term in the fantasy stories or games, so they can avoid any unnatural or awkwardness translation in the target language. The method that is used to collect the data is to determine the analysis unit which is the fantasy novel “Overlord”. Then, the unit is divided into smaller part which is the fantasy and game term. This research is qualitative research because it uses qualitative method to collect and analyze the data. The descriptive-qualitative approach is used in this research after the data sample is taken from all chapters in the novel before finally reducing the unnecessary and irrelevant data for this research. In analyzing the data, this research used a method where the data condensation, data display, and verifying and drawing conclusion are conducted. The result of this research shown that there are seven (7) translation techniques used in the Novel (translated version), they are: discursive creation (60), established equivalent (15), borrowing (184), Amplification (9), literal translation (118), modulation (29) and Particularization (4).